Refugees, Labour and Sectarianism in Syria under the French mandate (1921-1950) - Seda Altuğ (Revue des Mondes Musulmans et de la Méditerranée)
This article analyses the Syrianization of post–World War One refugees in Syria under the French mandate (1921–1946) through their involvement in two interrelated fields: the labour they spent in the opening up of the Jazira to agriculture, and their engagement in the highly contested politics of the mid-1930s. The scholarly literature on refugees in the Middle East usually operates within the fields of refugee, minority, and empire studies. This article aims to go beyond these fields by analysing the political and economic experiences of Christian and Kurdish refugees in French Syria. It demonstrates how which the French socio-economic project of making the Jazira was appropriated by local residents through labour and politics. It demonstrates how these refugee groups, with diverse histories of past violence and present dispositions, participated in pro-French colonial order and negotiated their terms of belonging to French-Syria in different ways in the decade following their arrival. It explores the centrality of the refugee question in the making of Syriannness both for the locals and the newcomers. Furthermore, the article investigates how ethnicity, religion and labour as the markers of Syrianness were negotiated through both the refugee issue and the involvement of former refugees in national politics.